Insights into coronary collateral formation from a novel porcine semiacute infarction model. Issue 2 (March 2018) - Krackhardt, Florian; Harnoss, Jonathan M.; Waliszewski, Matthias W.; Ritter, Zully; Granzow, Susanne; Felsenberg, Dieter; Neumann, Konrad; Lerman, Lilian O.; Hillmeister, Philipp; Gebker, Rolf; Paetsch, Ingo; Riediger, Fabian; et al.
Abstract : Background: For patients with severe ischemic heart disease, complete revascularization by a percutaneous coronary intervention or coronary artery bypass grafting is often not achieved and may still cause residual angina. In case of progressive coronary artery occlusions, therapeutic arteriogenesis constitutes a promising strategy for increasing blood supply to the ischemic myocardium. Whether the formation of collaterals in the hypofused myocardium is angiogenetic in nature or based on preformed coronary artery anastomoses remains debatable. The objectives of this research were (i) the development of an appropriate research methodology to study a humanoid animal semiacute infarction model with low mortality and (ii) to answer the question of whether collateral revascularization follows a pre-existing 'blueprint'. Materials and methods: A porcine model was chosen in which a step-wise vessel occlusion was performed by implantation of a copper stent into the distal left anterior descending artery. Vessel occlusion and collateral development were confirmed in vivo every 14 days up to day 56 by repeated coronary angiography and myocardial perfusion measurement using cardiac MRI. After the completion of the in-vivo imaging studies, animals were euthanized and collateral growth was evaluated using microcomputer tomography. Results: Our porcine model of semiacute noninvasive coronary artery occlusion confirmed the existence of preformed coronary anastomoses and the proliferation of functional vessels in hypoperfused myocardium. Repetitive intra-animal MRIs showed the functional impact of these growing collaterals. Conclusion: The confirmation of preformed coronary anastomoses during the process of collateralization (natural bypasses) offers a preclinical avenue to carry out arteriogenetic pharmaceutical research in patients with ischemic heart disease.